Endothelial Dysfunction in Diabetic Retinopathy - Gui, Fu; You, Zhipeng; Fu, Shuhua; Wu, Hongxi; Zhang, Yulan (Frontiers in Endocrinology, 2020)
Diabetic retinopathy (DR) is a diabetic complication which affects retinal function and results in severe loss of vision and relevant retinal diseases. Retinal vascular dysfunction caused by multi-factors, such as advanced glycosylation end products and receptors, pro-inflammatory cytokines and chemokines, proliferator‐activated receptor-γ disruption, growth factors, oxidative stress, and microRNA etc. These factors promote retinal endothelial dysfunction which results in the development of DR. In this review, we summarize the contributors in the pathophysiology of DR for a better understanding of the molecular and cellular mechanism in the development of DR with a special emphasis on retinal endothelial dysfunction.